Risk of Seizure Recurrence after First Seizure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The frequency of seizure recurrence in 283 children presenting with a first unprovoked seizure was studied in the Montefiore/Einstein Epilepsy Management Center, Bronx, NY; Yale University School of Medicine, New Haven, CN; and Columbia College of Physicians and Surgeons, New York, NY.